2022
DOI: 10.2166/wcc.2022.440
|View full text |Cite
|
Sign up to set email alerts
|

Future precipitation changes in the Central Ethiopian Main Rift under CMIP5 GCMs

Abstract: The purpose of this study is to predict future changes in precipitation in the Central Ethiopian Main Rift, which is vulnerable to climate change. The Long Ashton Research Station Weather Generator (LARS-WG) model was applied to project precipitation based on five global climate models (GCMs) (EC-EARTH, MIROC-ESM, HadGEM2-ES, INM-CM4, and CCSM4) from Coupled Model Intercomparison Project phase 5 (CMIP5) under two representative concentration pathways (RCP4.5 and RCP8.5) in the periods of 2041–2060 compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Compared to the climatological base period , the result of our study shows an increase in annual rainfall amount for the three RCPs and the three future periods except for RCP8.5 in the long-term period (2081-2100). Hailesilassie et al (2022) applied the Long Ashton Research Station Weather Generator (LARS-WG) model for precipitation projection based on five GCMs (MIROC-ESM, HadGEM2-ES, EC-EARTH, INM-CM4, and CCSM4) from CMIP5 under RCP4.5 and RCP8.5 for 2041-2060 compared to 1976-2005 baseline period in Central Ethiopia Main Rift area. The result showed that summer precipitation (often the rainy season) was predicted to fall while winter precipitation (often the dry season) was expected to climb in both scenarios; also, annual and spring precipitation was anticipated to decrease in most locations (Hailesilassie et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to the climatological base period , the result of our study shows an increase in annual rainfall amount for the three RCPs and the three future periods except for RCP8.5 in the long-term period (2081-2100). Hailesilassie et al (2022) applied the Long Ashton Research Station Weather Generator (LARS-WG) model for precipitation projection based on five GCMs (MIROC-ESM, HadGEM2-ES, EC-EARTH, INM-CM4, and CCSM4) from CMIP5 under RCP4.5 and RCP8.5 for 2041-2060 compared to 1976-2005 baseline period in Central Ethiopia Main Rift area. The result showed that summer precipitation (often the rainy season) was predicted to fall while winter precipitation (often the dry season) was expected to climb in both scenarios; also, annual and spring precipitation was anticipated to decrease in most locations (Hailesilassie et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Hailesilassie et al (2022) applied the Long Ashton Research Station Weather Generator (LARS-WG) model for precipitation projection based on five GCMs (MIROC-ESM, HadGEM2-ES, EC-EARTH, INM-CM4, and CCSM4) from CMIP5 under RCP4.5 and RCP8.5 for 2041-2060 compared to 1976-2005 baseline period in Central Ethiopia Main Rift area. The result showed that summer precipitation (often the rainy season) was predicted to fall while winter precipitation (often the dry season) was expected to climb in both scenarios; also, annual and spring precipitation was anticipated to decrease in most locations (Hailesilassie et al, 2022). In this study, Amhara's projected monthly and annual mean rainfall amount will be higher than that of the historical for all RCPs except for RCP 8.5 in the long-term future (2081-2100).…”
Section: Resultsmentioning
confidence: 99%
“…Projected to rise in global mean surface temperature under each of the evaluated emission scenarios throughout the twenty-first century between 0.3 and 4.8 and there will not be a uniform change in precipitation [5,32]. And the predicts were compatibility with many studies conducted around the world such as; Europe [14], North America [33], Africa [34][35][36][37], and Asia [38][39][40][41]. In Turkey, an increase in temperature and a decrease in precipitation rates were projected during the twenty-first century [42], while in Iran, the temperature rise was with variable trends in precipitation [43].…”
Section: Introductionmentioning
confidence: 82%